PENYALAHGUNAAN WEWENANG OLEH LURAH DALAM MEMBUAT SURAT KETERANGAN TANAH YANG BERFUNGSI SEBAGAI ALAS HAK ATAS TANAH BERDASARKAN SURAT EDARAN MENTERI DALAM NEGERI NOMOR 593/5707/SJ TAHUN 1984 - ENDANG SRI WAHYUNI (PREMISE LAW JURNAL, 2016)
The result of the research showed that the Certificate of Clarification of Land, issued by Lurah and acknowledged by Camat evidently caused dispute since there was overlapping ownership. It could not be solved by both Lurah and Camat so that the Circular Letter of the Minister of Internal Affairs No. 593/5707/SJ/1984 cancelled the authority of the Subdistrict Head in giving the license of clearing land. The fact, however, was that both Lurah and Camat had abused their authority which harmed other people; for examples, crime and violation on physical and judicial data and giving falsified data concerning the land done by Lurah, Camat, and the person who requested for the rights. It is recommended that the police should be pro-active in proving the crime to be processe. according to the prevailing regulations and not giving permission by arguing that it is not their authority since a land case belongs to the civil case. Keywords: Power Abuse, Lurah